Migration and Elites: The Formation of Elites in the Principality of Transylvania - Horn, Ildikó (Historical Studies on Central Europe, 2024)
This study examines the role and impact of migration on the formation and composition of the elite in the newly established Principality of Transylvania between 1556 and 1586, utilizing a prosopographical database compiled through extensive archival research. The new state was open to nobles fleeing the Ottoman conquest, as well as to those dissatisfied with Habsburg policies, offering peace, political prospects, and opportunities for career advancement in both government and military roles. Consequently, nearly 60 percent of the elite were newcomers, two-thirds of whom were migrant nobles, while one-third rose through social mobility. Characterized by smaller wealth, limited networks, and a tendency toward greater agility and risk-taking, the new elite were highly vulnerable. Their integration was hindered by the old elite’s reluctance to form dynastic ties. Only about 30 percent of the new families that entered the elite managed to maintain their positions long-term, across multiple generations, while a strikingly high number experienced only one or two generations of elite status. The analysis underscores the precarious nature of elite integration in early modern Transylvania and the complex dynamics of social mobility within a newly established state.